The Association of Surgical Complications with Glaucoma Surgery: A Systematic Review of Traditional and Minimally Invasive Procedures - Ria Andini Sutopo; Natasha Rismayana Wijayanti; Irsad Sadri (International Medical Journal Corp. Ltd, 2025)
INTRODUCTION: Surgical intervention is a cornerstone in the management of moderate to advanced glaucoma, a leading cause of irreversible blindness worldwide. The surgical landscape has evolved from traditional incisional procedures, such as trabeculectomy and glaucoma drainage device (GDD) implantation, to a diverse array of minimally invasive glaucoma surgery (MIGS) techniques. This evolution reflects a continuous effort to balance the efficacy of intraocular pressure (IOP) reduction with the risk of surgical complications. This systematic review aims to comprehensively synthesize and compare the complication profiles associated with this full spectrum of modern glaucoma surgeries. METHODS: A systematic literature search was conducted in PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library for studies published between January 2000 and October 2024. The search included randomized controlled trials (RCTs), prospective and retrospective cohort studies, and large case series reporting on complications of trabeculectomy, GDDs, and various MIGS procedures. Two independent reviewers performed study selection and data extraction. The methodological quality of RCTs was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool. Data on over 15 distinct intraoperative, early postoperative, and late postoperative complications were extracted and narratively synthesized. RESULTS: A total of 22 studies, including 8 major RCTs and 14 cohort studies, met the inclusion criteria. Traditional surgeries were associated with higher rates of severe complications. The 5-year results of the Primary Tube Versus Trabeculectomy (PTVT) Study showed that early postoperative complications were significantly more frequent after trabeculectomy than tube shunts (34% vs. 19%, p=0.013), though rates of late and serious complications were similar by year five. Comparative trials of GDDs, such as the Ahmed Baerveldt Comparison (ABC) and Ahmed Versus Baerveldt (AVB) studies, demonstrated that non-valved Baerveldt implants had a higher incidence of hypotony-related complications compared to valved Ahmed implants, which were more prone to hypertensive phase and encapsulation. MIGS procedures demonstrated a markedly more favorable safety profile. The 5-year HORIZON trial found the cumulative risk of subsequent incisional surgery was significantly lower with the Hydrus microstent plus phacoemulsification compared to phacoemulsification alone (2.4% vs. 6.2%, p=0.027), with no long-term adverse safety signals. The most common complications for MIGS were transient hyphema and IOP spikes. DISCUSSION: The evidence confirms a distinct trade-off between surgical efficacy and safety. Traditional procedures offer the most substantial IOP reduction but carry a significant risk of vision-threatening complications like bleb-related endophthalmitis and refractory hypotony. MIGS procedures offer a safer alternative, particularly for mild-to-moderate glaucoma, primarily reducing medication burden with minimal risk of severe adverse events. The choice of surgery is therefore dependent on a nuanced assessment of the patient's disease severity, target IOP, and risk tolerance. The inconsistent reporting of complications across studies remains a significant barrier to direct meta-analytic comparison. CONCLUSION: Glaucoma surgery encompasses a spectrum of procedures with widely varying complication profiles. While traditional surgeries remain indispensable for advanced disease, MIGS has fundamentally improved the safety paradigm for patients with less advanced glaucoma. Future research must adopt standardized definitions and reporting protocols for complications to allow for more robust evidence synthesis and to better guide clinical decision-making.